IbM Souvenir Making Workshop and Ways of Online Marketing in Bulu Lor Village - Buntoro, Ghulam Asrofi; Astuti, Indah Puji; Ariyadi, Dwiyono (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
This activity aims to realize the skills and independence in entrepreneurship for the community in Bulu Lor village, Jambon District, Ponorogo district. Utilizing potential opportunity situations, namely housewives and youth who are human resources in the village by providing briefing in the form of souvenirs to online product marketing assistance. The method in IbM activities is in the form of souvenir making training and mentoring for online marketing. The result of this activity is the improvement of entrepreneurial skills for the community, one way to improve the skills of housewives and youth in making souvenirs and introducing online marketing media. The training in making souvenirs from flannel cloth (key chains, brooches and flower bouquets) was attended by 24 participants. Although none of the participants present had ever made crafts from flannel and online marketing, after this training participants could make souvenirs from flannel (key chains, brooches and flower bouquets) and online marketing by utilizing social media (Facebook and Instagram).